2016
DOI: 10.3390/ijms17030395
|View full text |Cite
|
Sign up to set email alerts
|

Intronic Polymorphisms in the CDKN2B-AS1 Gene Are Strongly Associated with the Risk of Myocardial Infarction and Coronary Artery Disease in the Saudi Population

Abstract: Recent genome-wide association studies identified single nucleotide polymorphisms (SNPs) on the chromosome 9p21.3 conferring the risk for CAD (coronary artery disease) in individuals of Caucasian ancestry. We performed a genetic association study to investigate the effect of 12 candidate SNPs within 9p21.3 locus on the risk of CAD in the Saudi population of the Eastern Province of Saudi Arabia. A total of 250 Saudi CAD patients who had experienced an myocardial infarction (MI) and 252 Saudi age-matched healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…Chen et al (33) found that the polymorphism of CDKN2B-AS is very likely to be linked to intracranial aneurysm in Chinese population. Additionally, single nucleotide polymorphisms found in the intronic region of CDKN2B-AS1 have been revealed to be linked to coronary artery diseases (14). These findings are consistent with our results revealing elevated levels of lncRNA CDKN2B-AS1 in cerebral infarction lymphocytes, which may serve as a biomarker for cerebral infarction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Chen et al (33) found that the polymorphism of CDKN2B-AS is very likely to be linked to intracranial aneurysm in Chinese population. Additionally, single nucleotide polymorphisms found in the intronic region of CDKN2B-AS1 have been revealed to be linked to coronary artery diseases (14). These findings are consistent with our results revealing elevated levels of lncRNA CDKN2B-AS1 in cerebral infarction lymphocytes, which may serve as a biomarker for cerebral infarction.…”
Section: Discussionsupporting
confidence: 92%
“…Aberrant expression of lncRNA CDKN2B-AS1 has been reported to predict lung cancer (11). Furthermore, previous studies have indicated correlations between genetic variants of lncRNA CDKN2B-AS1 genetic variants and cardiovascular diseases and stroke (12)(13)(14). However, the underlying mechanism of lncRNA CDKN2B-AS1 in the pathogenesis of stroke remains largely unknown.…”
mentioning
confidence: 99%
“…[ 13 ] illustrated that heritability was 37.9% for all IS, 40.3% for large-vessel disease, 32.6% for cardio-embolic, and 16.1% for small-vessel disease. Although data accumulated from previous studies have identified associations between SNPs on chromosome 9p21 and the risk of CHD [ 14 , 15 , 16 , 17 , 18 ] and IS [ 19 , 20 ] in Caucasians, little is known about such associations among the Chinese populations. Moreover, many SNPs have still not been detected on the chromosome 9p21 region.…”
Section: Introductionmentioning
confidence: 99%
“…Among these variants, rs2383206 and rs10757278 displayed the closest association with CAD in an Indian population [127,128]. Investigation of CAD in a Saudi population identified four SNPs including rs564398, rs4977574, rs2891168, and rs1333042 associated with CAD/MI [129]. The first large case-control study (PROMIS) of a Pakistan population concluded that six (rs1333049, rs10757274, rs4977574, rs2891168, rs1537372 and rs9632885) of eighty-nine investigated SNP in the 9p21.3 locus were associated with MI [130].…”
Section: Discussionmentioning
confidence: 99%